Pemberdayaan Kelompok Tani dalam Penguatan Ekonomi Rumah Tangga Melalui Edukasi Budidaya Sayuran Pekarangan di Kelurahan Buntu Burake - Ellyn Patadungan; Oktavianus Pasoloran; Ade Lisa Matasik; Marsanda Delvi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The utilization of home yard land is one of the efforts that can be undertaken to improve household food security and economic resilience. However, in Buntu Burake Village, the utilization of home yards has not been optimal due to the limited knowledge of the community regarding cultivation techniques and simple farm management. This activity aims to empower the community and farmer groups through education on home yard vegetable cultivation as well as strengthening household-scale farm management. The method used is a participatory and applicative approach that actively involves the community in the planning, implementation, and evaluation processes of the program. The activities were carried out through socialization on yard utilization, training on vegetable cultivation using raised bed technology, and education on farm business analysis and simple financial record-keeping. The results of the activity indicate an increase in the community's knowledge and skills in utilizing home yards productively. The community has begun to apply vegetable cultivation techniques in their yards and understand the economic potential of harvests that can be used for household consumption or sold to surrounding communities. This program provides positive implications for improving household food security and strengthening the household economy in a sustainable manner.